SCROLLING AND SUSTAINED ATTENTION: HOW SOCIAL MEDIA INFLUENCE SUSTAINED ATTENTION OF HIGH SCHOOL STUDENTS - Rajeswari, N; Vakkil, M (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Social media is one of the powerful tools for connecting with people and sharing ideas and information. The utilization of online social media platforms for connecting with family, relatives, peers, colleagues, and others is encompassed within the concept of social networking. These platforms, which serve both social and business functions, are accessible through a range of websites. (Dr. Sadaf Mustafa, 2018) Valuable information is provided to users by social media platforms such as Facebook, YouTube, Instagram, and LinkedIn etc. But it diverts students from their studies. Following the COVID-19 pandemic, heightened levels of time are being dedicated by students to social media platforms. Because it provides additional opportunities for connecting with other people. In this study, the researcher analysed the impact of social site on sustained attention with respect to gender and geographical area. The study, which included 105 participants, entailed the development of a questionnaire aimed at investigating the influence of various elements of social media on the capacity of school students to sustain their attention. It was found that students’ sustained attention is negatively affected by social media, and individuals from diverse genders and geographical areas engage with social media for a variety of purposes.